Dissipation of carbendazim in mango after pre- and post-harvest treatments (The Journal of Plant Protection Sciences, 2020)
Dissipation of carbendazim was evaluated in mango fruit after pre as well as post harvest applications. Two pre harvest sprays of carbendazim @ 0.05 and0.1 per cent were given to mango fruit (cv. Chausa) at 10 days interval in such a way that last spray fell 12 days prior to harvest to control post harvest diseases viz., anthracnose (Colletotrichum gloeosporioides) and stem end rot (Lasiodiplodia theobromae). Carbendazim dissipated to 1.01 and 2.14 mg kg–1 in mature whole fruit after harvest (12 days after second spray) at 0.05 and 0.1 per cent concentrations, respectively, following first order rate kinetics. The corresponding values in fruit pulp after 12 days were 0.57 and 1.26 mg kg–1. In another experiment, cold water dip treatment in carbendazim solution @ 0.05 and 0.1 percent was given for 10 min to a separate lot of fruit having no pre harvest spray. Dissipation of carbendazim in whole fruit again followed first order rate kinetics with 0.92 and 2.06 mg kg–1 of the fungicide recovered after 10 days of storage from 0.05 and 0.1 percent doses, respectively. The corresponding values in fruit pulp after same days of storage were 0.51 and
Keywords: C a r b e n d a z i m; dissipation; mango; pre-harvest spray; post harvest dip